2010
DOI: 10.1111/j.1601-0825.2010.01665.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis case definition affects the association with renal function in kidney transplant recipients

Abstract: Aim The aim of this analysis is to investigate the association between periodontal status and renal allograft function in a cohort of renal transplant patients using different periodontitis case definitions. Material & Methods 58 kidney transplant patients were included. The subjects were classified into two groups, deterioration or stable/improvement of renal allograft function as expressed by the difference in glomerular filtration rate (GFR) between two time points at least 6 months apart. Chronic periodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 52 publications
2
21
0
3
Order By: Relevance
“…Similar to previous studies in dialysis patients, we did not observe an association between periodontal disease measures and CRP in our CKD study participants (as opposed to subjects without CKD) [29,43]. Ioannidou et al [44] found an association between a modified definition of periodontitis with mild elevation of CRP (>0.3 mg/dl) in subjects with CKD but not based on the standard AAP/CDC definition. These previous studies did not explore the association between leukocytosis and periodontitis in subjects with CKD.…”
Section: Discussionsupporting
confidence: 73%
“…Similar to previous studies in dialysis patients, we did not observe an association between periodontal disease measures and CRP in our CKD study participants (as opposed to subjects without CKD) [29,43]. Ioannidou et al [44] found an association between a modified definition of periodontitis with mild elevation of CRP (>0.3 mg/dl) in subjects with CKD but not based on the standard AAP/CDC definition. These previous studies did not explore the association between leukocytosis and periodontitis in subjects with CKD.…”
Section: Discussionsupporting
confidence: 73%
“…Salienta-se a necessidade de melhor abordagem para saúde bucal pré-transplante, visto associação com o aumento do risco cardiovascular 11 e a redução da sobrevida do enxerto renal 10 .…”
Section: Discussionunclassified
“…Estudos demonstram que a doença periodontal também atinge a DRC, incluindo a deteriorização mais rápida da função renal nos enxertos [10][11][12] . Micro-organismos relacionados à periodontite afetam a reologia sanguínea e contribuem para aceleração de doenças sistêmicas ou locais que levam à mortalidade prematura em pacientes em diálise 13 .…”
unclassified
“…First, compared with previous studies (Kshirsagar et al ., 2005; Fisher et al ., 2008), we used a more recent periodontitis case definition (Page and Eke, 2007), which has been adopted in official US public health publications on national prevalence of periodontitis (Dye et al ., 2007). Our group has shown previously that the choice of periodontitis case definition could affect associations with renal function (Ioannidou et al ., 2010). Furthermore, unlike prior studies (Fisher et al ., 2008), we limited our analysis to dentate adults, since we were unable to determine the edentulism frequency attributed to periodontitis.…”
Section: Discussionmentioning
confidence: 99%